The Influence of the Anchors' Professionalism and Attractiveness to Impulsive Buying in Livestream Shopping at Social Platforms: The Mediating Role of Emotional Factors - Truong Nu To , Giang; Le Minh , Phuc (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2024)
With the decent development of e-commerce, live-streaming shopping on social networking platforms has been blooming in recent years. Through the Stimulus-Organism-Response theory and the emotional contagion theory, this research aims to develop a comprehensive model of the anchors' professionalism, and attractiveness, and the impulsive buying of live stream viewers through the mediating role of emotional factors, thereby providing management implications for anchors and organizations. With 356 valid surveys collected using the convenient sampling method on Google Forms, data are analyzed using the PLS-SEM method. The results confirm the relationship between the anchors' professionalism and attractiveness, impulsive buying, and emotional factors. Given the limited research on this topic, this study has provided several managerial implications; at the same time, the results of this study also provide some contributions to the theoretical foundation as well as suggest further research direction.
Keywords: Livestream shopping; Impulsive buying; Professionalism; Attractiveness; Arousal; Pleasure